IB - Arvill, Robert ("Middlesex, Eng.", 1983)
The work of an expert who has had experience both of planning and of nature conservation at the local, governmental and international levels. With special reference to Britain, where all problems are aggravated by density of population, he outlines the policies and measures adopted by the official and voluntary bodies working in the fields. And to ensure, at any rate for our children, healthy land, clean air, pure water, and adequate spacer, the book proposes a strategy and a set of standards to enable man to shape his environment according to a worthwhile design.
Keywords: Man lnfluence on nature